The Effect of Leadership Style and Workload on Work Stress at Pt Bank Perkreditan Rakyat Buana Agribisnis Saribudolok - Winka Putri Simanjorang; Caecilia Try Wahyanti (Universitas Pendidikan Ganesha, 2021)
Workers find it difficult because the implementation of WFH has resulted in an increase in their workload and a workload that is not in accordance with their abilities. Worker. This causes work fatigue from mild to severe levels. The purpose of this study was to determine the effect of leadership style and workload on work stress, this type of research is quantitative research involving 35 respondents at PT Bank Perkreditan Rakyat Buana Agribisnis Saribudolok. The sampling technique used was non-probability sampling with a saturated sampling technique (census). because the population is small and the saturated sampling technique is a sampling technique when all members of the population are used as a sample of 35 people. The type of data used in this study is primary data which data directly provides to data collectors through questionnaires, and secondary data is data that is not obtained directly by researchers but is obtained from other people or parties. Data analysis used quantitative descriptive analysis techniques. The results show that leadership style is related to how employees guess the leadership style whether they like it or not. Bad leadership style causes employees to be unproductive and less creative so that it has an impact on career achievement so that employees are stressed with their work, while excessive workloads and short deadlines also greatly affect employee work stress. employees should be in accordance with the field and ability. So it can be said that the workload is a source of stress that affects the working conditions of employees.